Implementasi Bimbingan Belajar Mengulang Kelas dalam Menumbuhkan Kemampuan Akademik Siswa Baru di Madrasah Qudsiyyah Kudus - Yasfin, Moh Anwar; Ula, Ahmad Nilnal Munachifdlil (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Implementation of Class Repetition Guidance in Developing Academic Ability of New Students at Madrasah Qudsiyyah Kudus. This study aims to describe the implementation of repeating class tutoring in growing the academic abilities of new students at Madrasah Qudsiyyah Kudus. This study uses Field Research Methods (field research) with qualitative descriptive analysis techniques. The research data collected was then analyzed using a deductive approach and an inductive approach. The results showed that first, the guidance process in repeating classes for new students entering the Madrasah Qudsiyyah Kudus was that when they wanted to enter the Madrasah Tsanawiyah level, they had to repeat the first class in MI class voluntarily, even though they had graduated from SD or MI. Second, the tutoring for repeating the classes carried out at Madrasah Qudsiyyah is by grouping according to their abilities. Fourth, the tutoring model for repeating classes at Madrasah Qudsiyyah is carried out in groups by forming a separate curriculum which can focus on the basic salafiyah curriculum as a provision of salafiyah material at an advanced level. Fifth, this basic salafiyah guidance material is carried out by all teachers, not only burdened by counselors.Keywords: Guidance, Repeating Class, Madrasah Qudsiyyah